Deconstructing Obama : the life, loves, and letters of the first postmodern president - Cashill, Jack. (New York : Threshold Editions, 2011)
Deconstructing Obama tells the story of what happens when a citizen journalist discovers a game-changing reality that the media refuse to acknowledge. Despite their rejection, Cashill expanded his research into Obama's literary canon. As he came to see, if Dreams serves as sacred text, the poem'Pop' is the Rosetta stone, the key to deciphering Obama's shrouded past, his fragile psyche, and his uniquely cryptic political life. In unlocking that past, Cashill discovered that the story that Obama has been telling all his life varies from the true story in ways big and small. In fact, much of Obama's life story appears to be a wholly constructed fabrication, one that Jack Cashill'deconstructs' to show the world just who Barack Obama really is.
Includes bibliographical references (p. 295-319) and index.
Keywords: Obama, Barack -- Literary art; Obama, Barack -- Authorship; Obama, Barack -- Friends and associates